Low-Density Lipoprotein Cholesterol and Alzheimer's Disease: A Systematic Review and Meta-Analysis - Zhou, Zhike; Liang, Yifan; Zhang, Xiaoqian; Xu, Junjie; Lin, Jueying; Zhang, Rongwei; Kang, Kexin; Liu, Chang; Zhao, Chuansheng; Zhao, Mei (Frontiers in Aging Neuroscience, 2020)
Objective: To assess the association between low-density lipoprotein cholesterol (LDL-c) and risk of Alzheimer's disease (AD). Methods: Embase, Pubmed and Web of Science were searched until June 2019. Standard mean difference (SMD) with 95% confidence intervals (CI) was estimated using random-effects models. Results: Our meta-analysis of twenty-six studies revealed higher levels of LDL-c in AD than that of non-dementia controls (SMD=0.35, 95%CI 0.12~0.58, p<0.01). The meta-regression analysis on confounders showed that age (p<0.01, Adj R-squared=92.41%) and cardiovascular disease (p=0.01, Adj R-squared=85.21%), but not the body mass index, education, smoking, hypertension and diabetes mellitus, exerted an impact on the relationship between LDL-c and risk of ICH. Further subgroup analysis of age showed LDL-c levels in AD patients aged 60 to 70 were higher than that of non-dementia (60≤age<70: SMD=0.80, 95%CI 0.23~1.37, p<0.01); but no association between the SMD of AD in LDL-c and age over 70 was noted across the studies (70≤age<77: SMD=-0.02, 95%CI -0.39~0.34, p=9.0; 77≤age<80: SMD=0.15, 95%CI -0.17~0.47, p=0.35; ≥80: SMD=0.53, 95%CI -0.04~1.11, p=0.07). The concentrations of LDL-c during the quintile interval of 3~4 were positively associated with AD (121≤concentration<137: SMD=0.98, 95%CI 0.13~1.82, p=0.02; ≥137: SMD=0.62, 95%CI 0.18~1.06, p<0.01); whereas there was no correlation between AD and LDL-c within the quintile interval of 1~2 (103.9≤concentration<112: SMD=0.08, 95%CI -0.20~0.35, p=0.59; 112≤concentration<121: SMD=-0.26, 95%CI -0.58~0.06, p=0.11). Conclusions: Elevated concentration of LDL-c (>121 mg/dl) may be a potential risk factor for AD. This association is strong in patients aged 60-70 years, but vanishes with advancing age.